Influence of Mount-Foot Penetration Depth on the Quantification of Drying Strain - Fuller,James (Universidad del Bío-Bío, 2005)
The need for a drying stress indicator has previously been stated with some research in the past to this means. Given the recent successes in achieving this goal through monitoring shrinkage, the refinement and further understanding of the process was needed, specifically, the influence that penetration of the mount-foot had on the shrinkage data. Four different LVDTmounts were investigated in an attempt to acquire this information. The results indicated that the depth of penetration influenced the absolute value of shrinkage measured but did not influence determination of when peak stress occurred. The mounts mounted on the face of the board displayed the most stable and informative results